Pitting corrosion of Ni-Cr-Fe alloys at open circuit potential in chloride plus thiosulfate solutions - Becerra Araneda, Abraham Alexis; Kappes, Mariano Alberto; Rodríguez, Martín Alejandro; Carranza, Ricardo Mario (Pergamon-Elsevier Science Ltd, 2022)
Fil: Becerra Araneda, Abraham Alexis. Universidad Nacional de San Martín; Argentina. Comisión Nacional de Energía Atómica; Argentina